Women's Activities In Worship According to The Qur'an And Hadith - Subhan, Subhan; Sunarto, Andang; Arifin, Fajar (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
This paper examines the activities of worship for women that are permissible according to the Qur'an and Hadith in religious life. Her research focuses on women's activities in carrying out worship, both prohibited and permissible. This paper strengthens for women to worship in accordance with their nature so as not to carry out worship if the demand is forbidden to worship, it is permissible for women to worship to the mosque and is encouraged to study knowledge. This paper strengthens for women to worship in accordance with their nature so as not to carry out worship if the demand is forbidden to worship, it is permissible for women to worship to the mosque and is encouraged to study knowledge. This writing using the Literature Study method is a series of activities related to the method of collecting literature data, reading journals and articles about women's activities in worship according to the Qur'an and Hadith.Â  The results explain that women are forbidden to perform prayers, fasting, shiam and thawaf during menstruation and puerperium, but women can recite the Quran, make dhikr, pray, cut nails, cut hair and make out with their husbands. Then women are allowed to worship in mosques with a note that it does not contain slander and in accordance with their ethics and women are allowed to study knowledge.